Integrasi Fleksibilitas Strategis dan Kapabilitas Pembelajaran Organisasi sebagai Second-order Factor terhadap Kinerja Inovasi dan Perusahaan - Emiliana Sri Pudjiarti; Honorata Ratnawati Dwi Putranti (Universitas Proklamasi 45 Yogyakarta, 2020)
Tegal was once dubbed Japan's Indonesia, but the presence of the disruption era caused turbulence for Tegal metal SMEs (Small and Medium Enterprises). Many SMEs are not ready to face the changes that occur so that the bankrupt. Facing this situation, efforts are needed to maintain it. Efforts are made, among others, through the company's dynamic ability to manage the organization's internal resources. This study aims to examine the role of strategic flexibility and innovation performance as a mediating relationship between organizational learning capability and business performance. The objects in 224 SME’s of metal smelting and casting in Tegal were randomly selected. The tool tests the hypothesis using the structural eqution model (SEM). The results of the study concluded that strategic flexibility reinforces the positive effect of organizational learning capabilities on innovation performance and business performance, so that when strategic flexibility is high, business performance will increase higher, when associated with high innovation performance. Strategic flexibility is a source of competitive advantage that is supported by the role of management, and is driven by superior employees as organizational assets. So the company has the ability to be responsive and adaptive to changes that occur. This finding is a mechanism for navigating to face market turbulence and competition.